2012
DOI: 10.1038/nature10863
|View full text |Cite
|
Sign up to set email alerts
|

Goblet cells deliver luminal antigen to CD103+ dendritic cells in the small intestine

Abstract: The intestinal immune system is exposed to a mixture of foreign antigens from diet, commensal flora, and potential pathogens. Understanding how pathogen-specific immunity is elicited while avoiding inappropriate responses to the background of innocuous antigens is essential for understanding and treating intestinal infections and inflammatory diseases. The ingestion of protein antigen can induce oral tolerance, which is mediated in part by a subset of intestinal dendritic cells (DCs) that promote the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
739
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 810 publications
(763 citation statements)
references
References 31 publications
18
739
1
5
Order By: Relevance
“…Loss of proper mucin secretion may directly lead to chronic inflammation, as it has been shown that MUC2 deficient mice spontaneously develop chronic colitis [43]. Besides mucin production, goblet cells secretes cytokines such as IL-7 [44] and thus may exert immunoregulatory functions, and can also deliver luminal antigens to the underlying DCs [45]. Recent studies have shown that a newly identified Clchannel, bestrophin2 (BEST2), is expressed specifically by colonic goblet cells [46,47].…”
Section: Role Of Iecs In the Pathogenesis Of Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of proper mucin secretion may directly lead to chronic inflammation, as it has been shown that MUC2 deficient mice spontaneously develop chronic colitis [43]. Besides mucin production, goblet cells secretes cytokines such as IL-7 [44] and thus may exert immunoregulatory functions, and can also deliver luminal antigens to the underlying DCs [45]. Recent studies have shown that a newly identified Clchannel, bestrophin2 (BEST2), is expressed specifically by colonic goblet cells [46,47].…”
Section: Role Of Iecs In the Pathogenesis Of Ibdmentioning
confidence: 99%
“…Also, several cytokines that are produced by the proinflammatory lymphocytes, such as IL-1b or IL-6, may b Goblet cells produce MUC2 or TFF3 and maintain the mucosal layer to sequester gut microbes from the surface of the epithelial layer [39]. Expression of specific ion channels such as Bestrophin2 may support the proper function of the mucus layer [44,45]. Goblet cells can also interact with the lamina propria immune cells through antigen delivery or cytokine production [42,43].…”
Section: Mechanism Of Epithelial Repair In Ibdmentioning
confidence: 99%
“…Two cyclic displayed peptides dominated the selection, 13C and 28PP, representing 36 of 40 clones sequenced. given a selection of library phage clones in the presence of 2x10 4 fold excess of wild type phage.…”
Section: In Vivo Validation For Specificity Of the Selected Peptide Pmentioning
confidence: 99%
“…A certain population of these activated T cells moves from the PPs to MLNs through draining lymphatic ducts, then into the bloodstream through the thoracic duct, and finally accumulates in the intestinal mucosa (11,18). In contrast, lamina propriaderived CD103 + dendritic cells bearing luminal Ags captured in the intestine (19)(20)(21) migrate into MLNs (22,23), where they activate and induce a 4 b 7 expression on T N cells (24)(25)(26). Guttropic T cells generated in MLNs collect in the intestine via recirculation (11).…”
mentioning
confidence: 99%